The Existence of Periodic Solutions of Delay Differential Equations by E+-Conley Index Theory - Huafeng Xiao (Journal of Function Spaces)
In this paper, the E+-Conley index theory has been used to study the existence of periodic solutions of nonautonomous delay differential equations (in short, DDEs). The variational structure for DDEs is built, and the existence of periodic solutions of DDEs is transferred to that of critical points of the associated function. When DDEs are 2π-nonresonant, some sufficient conditions are obtained to guarantee the existence of periodic solutions. When the system is 2π-resonant at infinity, by making use a second disturbing of the original functional, some sufficient conditions are obtained to guarantee the existence of periodic solutions to DDEs.